2022
DOI: 10.48550/arxiv.2210.17176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Missing one-loop contributions in secondary gravitational waves

Abstract: We find several missing one-loop-order contributions in previous considerations about secondary gravitational waves induced at nonlinear order in cosmological perturbations. We consider a consistent perturbative expansion to third-order in cosmological perturbations, including higher-order interactions and iterative solutions ignored in the previous literature. Tensor fluctuations induced by the source with two scalar and one tensor perturbations are correlated with the first-order tensor fluctuation and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…However, such a requirement is only a tree-level statement. So far, understanding of inflation models accommodating PBH formation is very limited beyond tree-level, although it has been discussed in [117][118][119] for some specific models. It is important to ensure that one-loop correction is suppressed compared to the tree-level contribution, so that we can still trust the perturbation theory.…”
mentioning
confidence: 99%
“…However, such a requirement is only a tree-level statement. So far, understanding of inflation models accommodating PBH formation is very limited beyond tree-level, although it has been discussed in [117][118][119] for some specific models. It is important to ensure that one-loop correction is suppressed compared to the tree-level contribution, so that we can still trust the perturbation theory.…”
mentioning
confidence: 99%
“…Using Equations ( 28)- (32), we can calculate the power spectra of second-order induced scalar and energy density perturbations. The induced density perturbations will affect many physical processes at small scales, such as the formation of PBH [68] and high-order GW background [59]. By observing PBHs or higher-order GWs, we can constrain the power spectra of second-order induced density perturbations, thereby constraining inflationary models and the physical properties of primordial scalar and gravitational waves at small scales.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, the power spectra of second-order tensor perturbations induced by primordial scalar and tensor perturbations with large amplitudes were studied in Refs. [17,[59][60][61]. They considered the log-normal primordial scalar and tensor power spectra at small scales and found that primordial tensor perturbations have a very important effect on second-order induced tensor perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Since an early MD epoch can arise in such a varied array of models [21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]] (for a review, see ref. [42]), detailed studies of the associated GW signal are necessary.…”
Section: Introductionmentioning
confidence: 99%